1978
DOI: 10.1111/j.1751-1097.1978.tb07625.x
|View full text |Cite
|
Sign up to set email alerts
|

Quenching of Chlorophyll Fluorescence by Nitrobenzene

Abstract: Abstract—Nitrobenzene quenching of chlorophyll fluorescence in ethanol has been investigated. Steady state relative quantum yields have been measured and fluorescence decay rates were determined using both nanosecond photon counting and picosecond pulses from a mode‐locked Nd3+ glass laser. The fluorescence decay is described by 1(t)=I0 exp (‐t/τ−At1/2) the form predicted for decay governed by the kinetics of the continuum model of diffusion controlled reactions. From the parameters of the fluorescence decay, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…This relation is frequently found to give closer agreement with experimental decays than the exponential law in very fast kinetic studies and is predicted theoretically for the early stages of time-dependent diffusion processes and for Forster-type energy transfer to a random array (Beddard et at., 1978). Its significance in photosynthetic antennae must await more precise kinetic measurements as well as better information on the structure of these systems.…”
Section: Energy Transfir In the Antennasupporting
confidence: 76%
“…This relation is frequently found to give closer agreement with experimental decays than the exponential law in very fast kinetic studies and is predicted theoretically for the early stages of time-dependent diffusion processes and for Forster-type energy transfer to a random array (Beddard et at., 1978). Its significance in photosynthetic antennae must await more precise kinetic measurements as well as better information on the structure of these systems.…”
Section: Energy Transfir In the Antennasupporting
confidence: 76%
“…A more important feature is that nitrobenzene associates with fluorophores, including fluorescein, and thereby quenches the fluorescence 9. 14 Furthermore, this quenching mechanism can be utilized as a general strategy for the design of turn‐on fluorescence probes. It is envisioned that the fluorescein of the probe loses its fluorescence by the association with nitrobenzene, and this association inhibits the unwanted interaction between the ligand and fluorophore moieties, thereby leading to rapid protein labeling (Scheme ).…”
Section: Methodsmentioning
confidence: 99%
“…It is found that all nitroaromatics employed in the present study function as efficient quenchers. Moreover, it may be noticed that acceptors which exhibit larger K values quench the fluorescence strongly (larger K,, values) (Beddard et al, 1978). The possible kinetic scheme for the quenching mechanism can be written as…”
Section: Discussionmentioning
confidence: 99%
“…It has been known for some time that Chl forms CT complexes with quinones and nitroaromatics where the pigment essentially functions as a donor and quinones and nitroaromatics as acceptors (Connolly. 1981;Beddard et al, 1978;Seely, 1978). The fluorescence quenching studies of Chl by these a c c e p t o r s is d o c u m e n t e d ( N a t a r a j a n a n d Blankenship.…”
Section: Introductionmentioning
confidence: 99%